The transfer of unsterilized material from Mars to Phobos: Laboratory tests, modelling and statistical evaluation. (November 2019) - Patel, M.R.; Pearson, V.K.; Evans, D.J.; Summers, D.J.; Paton, S.; Truscott, P.; Pottage, T.; Bennett, A.; Gow, J.P.D.; Goodyear, M.D.; Mason, J.P.; Leese, M.R.; et al.
Abstract: Sample return missions to Phobos are the subject of future exploration plans. Given the proximity of Phobos to Mars, Mars' potential to have supported life, and the possibility of material transfer from Mars to Phobos, careful consideration of planetary protection is required. If life exists, or ever existed, on Mars, there is a possibility that material carrying organisms could be present on Phobos and be collected by a sample return mission such as the Japanese Martian Moons eXplorer (MMX). Here we describe laboratory experiments, theoretical modelling and statistical analysis undertaken to quantify whether the likelihood of a sample from Phobos material containing unsterilized material transferred from Mars is less than 10 −6, the threshold to transition between restricted and unrestricted sample return classification for planetary protection. We have created heat, impact and radiation sterilization models based on the Phobos environment, and through statistical analyses investigated the level of sterilization expected for martian material transferred to Phobos. These analyses indicate that radiation is the major sterilization factor, sterilizing the Phobos surface over timescales of millions of years. The specific events of most relevance in the Phobos sample return context are the 'young' cratering events on Mars that result in Zunil-sized craters, which can emplace a large mass of martian material on Phobos, in a short period of time, thus inhibiting the effects of radiation sterilization. Major unknowns that cannot yet be constrained accurately enough are found to drive the results – the most critical being the determination of exact crater ages to statistical certainty, and the initial biological loading on Mars prior to transfer. We find that, when taking a conservative perspective and assuming the best-case scenario for organism survival, for a 100 g sample of the Phobos regolith to be below the planetary protection requirement for unrestricted sample return, the initial biological loading on Mars must be <8.2 × 10 3 cfu kg -1 . For the planned MMX mission, a ∼10 g sample to be obtained from a 25–30 mm diameter core as planned would require an initial martian biological loading to be <1.6 × 10 4 cfu kg -1, in order to remain compliant with the planetary protection threshold